(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study evaluates vegetation conditions in Dangara District, Fergana Region, Uzbekistan, using Sentinel‑2 imagery acquired during May 2026. NDVI, EVI and SAVI indices were calculated in Google Earth Engine using JavaScript. The indices were compared to assess vegetation vigor, crop development and the influence of soil background. Results indicate that NDVI effectively identifies general vegetation patterns, EVI provides improved sensitivity in high-biomass areas, and SAVI reduces soil reflectance effects in sparsely vegetated agricultural lands. The findings demonstrate the importance of multi-index analysis for agricultural monitoring and sustainable land management.